2016
DOI: 10.1111/asj.12591
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and fluctuation in ciliate protozoan population in the rumen of cattle

Abstract: The purpose of this study was to investigate the diversity and fluctuation in the ciliate protozoan population in the rumen of cattle. DNA was extracted from the rumen of three ruminally cannulated, crossbred cattle and a polymerase chain reaction (PCR)-derived clone library was constructed, using a specific primer set targeting 18S ribosomal RNA genes of ciliate protozoa. DNA fragments of seven selected clones were validated for standard DNA of the protozoa-specific real-time PCR assay. Furthermore, populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In the current study, Entodinium was the predominate protozoa genus in the rumen, which was consistent with previous studies [6,77,78]. Entodinium has been characterized as a starch feeder.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, Entodinium was the predominate protozoa genus in the rumen, which was consistent with previous studies [6,77,78]. Entodinium has been characterized as a starch feeder.…”
Section: Discussionsupporting
confidence: 92%
“…in adult cattle. Abrar et al (2016) observed a large concentration of this eukaryote (80%) in adult animals (Holstein × Wagyu) fed with ryegrass straw and commercial concentrate. This ciliate was also recorded in high concentration diets (79%) for Martinele et al (2008) in crossbred Dutch-zebu cows receiving different concentrations of elephant grass (60-100%) and Ríspoli et al (2009) reported the occurrence of 85% of Entodinium spp.…”
Section: Categoriesmentioning
confidence: 92%
“…Other research has also recorded higher occurrences of Entodinium spp. in adult cattle (Abrar et al, 2016). Observed a large concentration of this protozoa (80 %) in adult animals (Holstein × Wagyu).…”
Section: Discussionmentioning
confidence: 87%